National Security and Cyber Defense in the Rise of Artificial Super Intelligence - Md. Abul Mansur (European Scientific Journal, ESJ, 2025)
The rise of Artificial Superintelligence (ASI) marks a pivotal transformation in the global cybersecurity landscape. Surpassing the limitations of Artificial General Intelligence (AGI), ASI introduces systems capable of autonomous reasoning, instantaneous threat response, and strategic adaptability far beyond human capability. While its defensive applications hold immense promise, the offensive potential of ASI presents an equally formidable challenge. Real-world events such as the SolarWinds infiltration in 2020 and the NotPetya ransomware outbreak in 2017 illustrate the devastating impact of AI-augmented cyber operations on national infrastructure and global commerce. These cases underscore the urgency of preparing for more advanced threats as ASI technology matures. This paper investigates the dual role of ASI in modern cyber conflict through a mixed-method approach combining empirical case study analysis, comparative evaluation of AGI and ASI capabilities, and scenario-based modeling. Particular emphasis is placed on examining how ASI alters traditional cyberattack vectors and reshapes defensive paradigms. The study further explores the integration of advanced countermeasures, including blockchain-backed data integrity systems, zero-trust security models, and autonomous deception frameworks. In addressing the wider implications, the paper also considers the ethical, legal, and governance challenges posed by opaque, autonomous decision-making in high-stakes security contexts. By mapping current capabilities and foreseeable trajectories, the analysis offers a policy-oriented framework to guide the responsible development and secure integration of ASI into national defense infrastructures.